The Reality of the Experience of Teaching Mathematics Remotely from the Perspectives of Teachers ‎and Secondary School Graduates during the Corona Pandemic - Barzanji, Salwa Salem (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to explore the experiences of teaching mathematics remotely from the perspectives of teachers and secondary school graduates during the Corona pandemic in Medina and to locate their levels of satisfaction with these experiences. The researcher designed two questionnaires, each consisting of (31) phrases, and was divided into four main sections. The study sample was (75) male and female teachers and (163) male and female students for a total of (238) participants. The results of the Independent sample T-test indicated statistically significant differences in favor of teachers regarding three sections: teaching and learning the mathematical content, classroom communication, and technical aspects in the e-environment, with mean scores of (4.04), (3.98), and (4.17), respectively. Moreover, the results also showed that no statistically significant differences were found regarding “evaluative aspects of teaching mathematics in an e-environment,” although the teachers demonstrated a very high mean score (4.21), and the students also revealed a high mean score (4.05). The results also reported that the level of satisfaction of secondary school teachers with the experience of teaching and learning mathematics remotely during the Corona pandemic was (Satisfied) with a mean score of (2.40). On the other hand, the level of satisfaction of secondary school graduate students with the experience of teaching and learning mathematics remotely was (Somewhat Satisfied) with a mean score of (2.12). The study concluded with some recommendations, such as the need to produce and design interactive software for teaching mathematics in Arabic at all stages of public education and develop interactive e-versions of mathematics curricula that work in parallel with the textbooks.